Membangun Karakter Bangsa Melalui Kepramukaan - Renilda Manis Da Gomez; Elviana Pona Rato; Donatus Datoq; Marwan Marwan; Wihelmus Sede; Fitrah Hamzah (Jurnal Ilmiah Dan Karya Mahasiswa, 2025)
Scouting is one of the non-formal education methods that plays an important role in building the character of the younger generation. This research aims to analyze the contribution of scouting in character formation, identify the benefits obtained by scout members, and assess the challenges faced in the modern era. Through a literature study approach and analysis of the latest data obtained from books, journals, and articles, this research found that scouting activities not only teach practical skills but also moral values such as discipline, responsibility, and leadership. Participation in scouting has been proven to enhance social skills and a sense of patriotism among teenagers. However, scouting also faces significant challenges, including the lack of interest from the younger generation who are more focused on digital activities. To remain relevant, scouting needs to adopt innovative methods that appeal to the younger generation, such as utilizing digital technology in its programs. This research provides recommendations for the development of more effective scouting programs, thereby attracting more participants and enhancing their impact on national character education.